Evaluation of Osteoporosis in Hemophilic Arthropathy Patients: Correlation with Disease Severity and Serum Trace Minerals - Eiman Mahmoud Ghaniema; Sahar Fathi Ahmed; Irene Raouf Amin; Maryse Soliman Ayoub (Journal of Osteoporosis)
Objective. To find out the presence of osteoporosis in hemophilic arthropathy patients and its correlation with clinical severity and serum levels of magnesium, copper, and zinc. Methods. Joint score, functional assessment score, bone densitometry, and serum magnesium, copper and zinc were done in twenty male hemophilic arthropathy patients and twenty controls. Results. There was highly significant lower Z scores of lumbar spine and neck of femur in patients versus controls (P<0.011). Z score of neck of femur correlated negatively with total joint score (P=0.013) and functional assessment score (P=0.011). Serum levels of copper and zinc correlated positively with Z score of neck of femur (P=0.004, P=0.001, resp.). Conclusion. Osteoporosis represents a frequent concomitant observation in hemophiliacs. Screening of young hemophiliacs for osteoporosis is recommended with measuring serum levels of magnesium, copper, and zinc for better management of the disease.